2023
DOI: 10.2196/45920
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Initial Adoption of the Heart Observation App for Infants With Congenital Heart Disease: Qualitative Study

Abstract: Background Approximately 1% of all infants are born with a congenital heart disease (CHD). Internationally CHD remains a major cause of infant death, some of which occur unexpectedly after a gradual deterioration at home. Many parents find it difficult to recognize worsening of symptoms. Objective This study aims to report the acceptability and initial adoption of a mobile app, the Heart Observation app (HOBS), aiming to support parents’ understanding a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A qualitative study conducted by Hjorth‐Johansen et al 15 examined an application designed for infants with congenital heart disease. This study demonstrated the importance of information addressing treatment‐related issues, such as post‐heart surgery recommendations and shunts.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A qualitative study conducted by Hjorth‐Johansen et al 15 examined an application designed for infants with congenital heart disease. This study demonstrated the importance of information addressing treatment‐related issues, such as post‐heart surgery recommendations and shunts.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other studies have highlighted the benefits of mobile applications in providing education and support for mothers of children with congenital heart disease during their home care. 9 A qualitative study conducted by Hjorth-Johansen et al 15 examined an application designed for infants with congenital heart disease. This study demonstrated the importance of information addressing treatment-related issues, such as post-heart surgery recommendations and shunts.…”
Section: Education Related To Surgerymentioning
confidence: 99%
See 3 more Smart Citations